2021
DOI: 10.1002/adfm.202104913
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Defect Limit to the Growth of Orthorhombic HfO2 and (Hf,Zr)O2 with Strong Ferroelectricity: First‐Principles Insights

Abstract: It is believed that promoting the fraction of ferroelectric orthorhombic phase (o-phase) through O-poor growth conditions can increase the spontaneous polarization of HfO 2 and (Hf,Zr)O 2 thin films. However, the first-principles calculations show that the growth may be limited by the easy formation of point defects in the orthorhombic and tetragonal phases of HfO 2 , ZrO 2 , and (Hf,Zr)O 2 . Their dominant defects, O interstitial (O i ) under O-rich conditions and O vacancy (V O ) under O-poor condition, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 59 publications
2
38
0
1
Order By: Relevance
“…[326,327] Therefore, the formation of o-phase-a metastable phase in HfO 2 -based material-can be driven by manipulating the energy landscape during the fabrication process. The capsulation of HfO 2 thin film before the annealing procedure is indeed only one method to stabilize o-phase, and it is a wellestablished fact that the total energy of thin films can be strongly affected by the grain boundaries, [328,329] film thickness, [330][331][332] point defects (especially oxygen vacancies in case of oxide thin films), [333][334][335][336][337][338][339][340][341][342][343][344][345] film composition, [346][347][348][349][350][351] the type of capping electrode, [326,327] and deposition and annealing conditions. [311,314,332] During the last decade, numerous investigations were conducted to understand the formation of the o-phase and optimize the fabrication conditions to provide a driving force toward stabilization of the o-phase.…”
Section: Origin Of Ferroelectricity In Hafnium Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…[326,327] Therefore, the formation of o-phase-a metastable phase in HfO 2 -based material-can be driven by manipulating the energy landscape during the fabrication process. The capsulation of HfO 2 thin film before the annealing procedure is indeed only one method to stabilize o-phase, and it is a wellestablished fact that the total energy of thin films can be strongly affected by the grain boundaries, [328,329] film thickness, [330][331][332] point defects (especially oxygen vacancies in case of oxide thin films), [333][334][335][336][337][338][339][340][341][342][343][344][345] film composition, [346][347][348][349][350][351] the type of capping electrode, [326,327] and deposition and annealing conditions. [311,314,332] During the last decade, numerous investigations were conducted to understand the formation of the o-phase and optimize the fabrication conditions to provide a driving force toward stabilization of the o-phase.…”
Section: Origin Of Ferroelectricity In Hafnium Oxidementioning
confidence: 99%
“…Recently, Wei et al [333] investigated the effect of oxygenrelated defects, that is, oxygen vacancy and oxygen interstitial on the ferroelectric features of HfO 2 based thin films. Their calculations showed that the formation energy of o-phase reduced upon the introduction of oxygen vacancies; however, the existence of high density of vacancies in o-phase can cause the disordering of dipole moments, increase in polarization b) C-V characteristics of the same film stack where crystallization was induced after top electrode deposition by an RTA ("capped" crystallization).…”
Section: Oxygen Vacancymentioning
confidence: 99%
“…O and structural polymorphism kinetics are expected to contribute to performance instability issues including wake-up and imprint. In a pristine ferroelectric HfO 2 -based capacitor at room temperatures, V 0 O is the dominant type of oxygen vacancy, as supported by recent DFT calculations [59] and experiments [40]. Therefore, V 0…”
Section: The Intricate Coupling Between V 2+mentioning
confidence: 73%
“…The dominant orthorhombic phase observed on TiN is therefore consistent with a reduced forming/set voltage relative to monoclinic films grown on Pt without need for reducing the activation enthalpy. The oxygen vacancy formation energy in both phases is similar at the same Fermi level position [67], so the ionization energy is kept the same when fitting the datasets. Only a slight increase in capture cross section (from 1 × 10 −14 cm 2 to 2 × 10 −14 cm 2 ) was needed to fit the Pt devices.…”
Section: Predictive Capability Of Modelmentioning
confidence: 99%